Analisis Pengaruh Pembelajaran Sosial Emosional (PSE) terhadap Karakteristik Peserta Didik Kelas II di SDN Kalicari 01 - Septiaji Evi Natanti; Ida Dwijayanti; Kusen Kusen (Journal on Education, 2024)
This research aims to determine the influence of social emotional learning on student characteristics. This type of research uses descriptive research using a qualitative research approach. Data collection in this research used observation, interviews and documentation. The data analysis techniques used are data reduction, data display, and data verification/conclusion. The results of the research show that there is a positive influence, namely that students are able to interact well, have an empathetic attitude towards other people, reduce conflict with friends, and respect differences with peers, teachers and the surrounding community. Thus it can be concluded that Social Emotional Learning and character education are important aspects in the overall development of students because they can provide a solid foundation for understanding, appreciating and dealing with various life situations.